Efficiency of the organization of personal choice in the development by the students of the methods of creative activity - E. G. Evdokimova; I. A. Bukharova (Вестник университета)
The reasons for introducing opportunity of a choice in lesson structure as an intrinsic feature of teacher personality has been represented. And it demands relevant organization in the process of professional training. The correlation between the readiness of a teacher to act under conditions of uncertainty and the readiness of students to choose ways of creative activities has been substantiated. The basic aspects of organization of students' personal choice of ways of creative activities, for example, heuristic tasks, have been examined. The factors, which raise or lower the effectiveness of organization of that choice, have been highlighted.